Formation of a comprehensive system of state management of international transportation of Ukraine - Мамаева, А. Н. (Proceedings of National Aviation University (archive), 2020)
The urgency of the formation of an integrated system of statemanagement of international transport of Ukraine and its impact on the efficiency  functioning of transport structures serving foreign tradecountry. The methods of state management of international transportation, which can be the basis of this system